Rapid design prototyping and tooling - Lee, Yong Tsui. (2008)
The objectives of this research programme are to: 1. Establish the fundamental infrastructure - software and hardware - required to support advanced research in and application of rapid design, prototyping and tooling. 2. Facilitate research and development to solve the problems identified, including integration of the processes involved and the study of new methods for rapid prototyping and tooling. 3. Develop new applications using rapid prototyping, especially medical applications. 4. Establish the core expertise in the field and generate new knowledge and processes. 5. Produce trained personnel who can be deployed in local industry. 6. Serve as a resource centre for Singapore industries and institutions in the use of the technologies.